The awkward black man ebook Stories. - Mosley, Walter (2020)
A new collection of short fiction from the Edgar Award-winning author of Devil in a Blue Dress and Trouble is What I Do . With his extraordinary fiction and gripping television writing, Walter Mosley has proven himself a master of narrative tension.  The Awkward Black Man  collects seventeen of Mosley’s most accomplished short stories to showcase the full range of his remarkable talent. Touching, contemplative, and always surprising, these stories introduce an array of imperfect characters—awkward, self-defeating, elf-involved, or just plain odd. In The Awkward Black Man , Mosley overturns the stereotypes that corral black male characters and paints subtle, powerful portraits of unique individuals. In "The Good News Is," a man’s insecurity about his weight gives way to illness and a loneliness so intense that he’d do anything for a little human comfort. "Pet Fly," previously published in the  New Yorker , follows a man working as a mailroom clerk—a solitary job for which he is overqualified—and the unforeseen repercussions he endures when he attempts to forge a new connection. And "Almost Alyce" chronicles failed loves, family loss, alcoholism, and a Zen approach to the art of begging that proves surprisingly effective.